The frequency of peripheral neuropathy in a group of HIV positive patients in Brazil Freqüência da neuropatia periférica no Brasil em um grupo de pacientes HIV positivo - Claudia Zanetti; Gilberto M. Manzano; Alberto A. Gabbai (Arquivos de Neuro-Psiquiatria)
Peripheral neuropathy is a common neurological complication occurring in asymptomatic and symptomatic stages of HIV infection. The most common syndromes are distal symmetric polyneuropathy, inflammatory demielinating polyneuropathy, poliradiculopathy, mononeuropathy, mononeuropathy multiplex and autonomic neuropathy. PURPOSE: To evaluate the frequency of peripheral neuropathy in a group of HIV seropositive outpatients in São Paulo, Brazil. METHOD: Over a period of 17 months, 49 HIV+ patients where evaluated clinically. Laboratory analysis and electroneuromyography were requested to all patients. RESULTS: >Thirty four (69.4%) of the 49 patients had the diagnosis of peripheral neuropathy established on clinical grounds. The most common sign was impairment (97.1%) of sensibility. Thirteen (33.3%) of the 39 that were subjected to electroneuromyography had features of peripheral neuropathy, being a sensitive-motor axonal neuropathy the most common. No abnormalities were found in the laboratory analysis performed in 42 patients, except in four who had VDRL positive. CONCLUSION: A peripheral neuropathy was frequently found upon clinical examination in our group of HIV positive individuals. A neuropatia periférica é complicação neurológica comum, podendo ocorrer nas fases assintomáticas e sintomáticas da infecção pelo vírus da imunodeficiência humana (HIV). As síndromes mais comuns são a polineuropatia distal simétrica, polineuropatia desmielinizante inflamatória, polirradiculopatia, mononeuropatia, mononeuropatia múltipla e neuropatia autonômica. OBJETIVO: Avaliar a freqüência da neuropatia periférica em um grupo de pacientes HIV positivo em São Paulo, Brasil. MÉTODO: Em um período de 17 meses, foram avaliados clinicamente 49 pacientes HIV positivos. Foram solicitados exames laboratoriais e eletroneuromiografia (ENMG) para todos os pacientes. RESULTADOS: Foi estabelecido o diagnóstico clínico de neuropatia periférica em 34 (69,4%) dos 49 pacientes. O sinal neurológico mais comum foi a alteração da sensibilidade (97,1%). Treze (33,3%) dos 39 pacientes que realizaram a ENMG tiveram o diagnóstico de neuropatia periférica, sendo a neuropatia sensitivo-motora axonal o achado mais comum. Não foram encontradas alterações significativas nos exames laboratoriais (42 pacientes realizaram os exames), com exceção de quatro pacientes em que o VDRL foi positivo. CONCLUSÃO: A neuropatia periférica foi um achado freqüente no grupo de pacientes HIV positivo estudados clinicamente.